Exploring Design Thinking for Innovation in Higher Education - Oluwatoyin Ayodele AJANI; Shoba RATHILAL (Social Sciences and Education Research Review)
This paper reviews current research about the use of design thinking in inspiring innovation at higher education institutions. One such aspect of design thinking, a human-centered approach, has found a foothold in various industries, including the educational sector, with many perceiving design thinking as the way to tackle complex matters. This study synthesizes different possible variables related to the applicability of higher education design thinking. Important among these are empathy, collaboration, and iteration, as well as their role in enhancing innovative growth among faculty, students, and staff. It looks at the extent of the culture of an organization, the openness and support of leadership, and choices, while at the same time examining the stumbling blocks that would face the regular diffusion of design thinking in educational practices, e.g. the resistance to change, the absence of support within the educational environment, and reluctance in training. This work, then, is very much pertinent to the broader understanding of design thinking as a lever for innovation in higher education by practitioners, policymakers, and researchers.